Kabupaten Kota Layak Anak - Hamid Patilima (Jurnal Kriminologi Indonesia, 2017)
The CRC was transformed of the legal language to policies, programs, and activities through the Child Friendly City (KLA). KLA is regencies / cities that have a development system based on the rights of children through the integration of the commitment and resources of governments, communities, businesses and the media which is thoroughly planned and sustained in policies, programs and activities to guarantee the fulfillment of children’s rights.KLA was first inspired by Kevin Lynch’s research that was later developed by Louise Chawla. The research was encapsulated in the concept of Child Friendly City Initiative. Continuously in Indonesia, the development of KLA is organized and established by the Child Protection Act.The core of the KLA for criminology development is to be the platform for ideas trial, concepts, models, and technologies that are related to criminology, practices, concepts and theories about the protection, respect, fulfillment and promotion toward children’s rights.Kata Kunci: Anak, Kota, Kabupaten, Layak Anak, Hak Anak, Perlindungan Anak, Konvensi